Respuesta :

Answer:

5x-1

Step-by-step explanation:

f(x) = 3x - 2

g(x) = 2x + 1

f(x) + g(x) = 3x-2 +2x+1

                Combine like terms

                = 5x-1

Answer:

(f+g)(x)=5x-1

Step-by-step explanation:

To find (f+g)(x), add f(x) and g(x)

f(x)+g(x)

We know that f(x) is equal to 3x-2 and g(x) equals 2x+1.

f(x)=3x-2

g(x)=2x+1

(3x-2)+ (2x+1)

Combine like terms. Add all the terms with a variable, then all the terms without a variable

(3x+2x)+(-2+1)

5x+(-2+1)

5x-1

(f+g)(x)=5x-1

ACCESS MORE